Cytology of small-cell carcinoma of the uterine cervix in serous effusion: A report on two cases - Khunamornpong S. (2014)
Cytologic features of 2 cases of small-cell carcinoma of the uterine cervix in the body fluid are described. Case 1 was a 34-yr-old woman with a stage IIA cervical tumor. Pleural effusion developed 6 mo after initial diagnosis. Case 2 was a 38-yr-old woman with a stage IB tumor. Ascites was detected 11 mo after hysterectomy. Histologically, both cervical tumors were indistinguishable from small-cell carcinoma of oat-cell type in the lungs or other sites. Cytologically, the tumor cells in the pleural effusion of case 1 had characteristic features of small-cell carcinoma, including nuclear molding. However, almost all tumor cells in the ascites of case 2 showed a single-cell pattern mimicking malignant lymphoma. Mitotic figures and karyorrhetic bodies were occasionally seen. Nuclear molding was rarely identified. Small-cell carcinoma should be included in the differential diagnosis of malignant effusions containing lymphoma-like cells. © 2001 Wiley-Liss, Inc.